Six Sigma Leader : How Top Executives Will Prevail in the 21st Century - Pande, Peter S. (McGraw-Hill's AccessEngineering., 2007)
The Six Sigma Leader defines successful leadership in the 21st century. With illustrative examples and proven strategies such as "The 10 Second Rule" (taking that extra time to make sure you're asking the right questions to get the information you need), this book offers techniques that link leadership improvement to real business results, and explores, Six Sigma Leadership: the core principles of Six Sigma leadership and the 21st-century, challenges of balance and flexibility, Change and Constancy: the role of change in leadership and how to achieve greater return on your change portfolio, Certainty and Doubt: the myth of leader infallibility and ways to confidently combine facts and intuition, Speed and Deliberateness: the benefits and perils of "speed at all costs" and a set of key disciplines that enable greater speed, Teamwork and Independence: the sources of organizational barriers and the leadership practices that can eliminate them, Now, Tomorrow and Next Year: the management of business change by different time horizons: short-, mid-, and long-term, Customer First?and Last: why customers are so critical, yet can also be a detriment to long-term business health, Bringing Six Sigma Leadership to Life: the factors likely to favor and inhibit successful adoption of Six Sigma leadership, Driven by a vision of great leadership, The Six Sigma Leader is an essential resource for managers at all levels and a call to action for any leader seeking to create a legacy of achievement.